The somatic mutation landscape of normal gastric epithelium - Tim H. H. Coorens; Grace Collord; Hyungchul Jung; Yichen Wang; Luiza Moore; Yvette Hooks; Krishnaa Mahbubani; Simon Y. K. Law; Helen H. N. Yan; Siu Tsan Yuen; Kourosh Saeb-Parsy; Peter J. Campbell; et al. (Nature, 2025)
Abstract The landscapes of somatic mutation in normal cells inform us about the processes of mutation and selection operative throughout life, providing insight into normal ageing and the earliest stages of cancer development 1 . Here, by whole-genome sequencing of 238 microdissections 2 from 30 individuals, including 18 with gastric cancer, we elucidate the developmental trajectories of normal and malignant gastric epithelium. We find that gastric glands are units of monoclonal cell populations that accrue roughly 28 somatic single-nucleotide variants per year, predominantly attributable to endogenous mutational processes. In individuals with gastric cancer, metaplastic glands often show elevated mutation burdens due to acceleration of mutational processes linked to proliferation and oxidative damage. Unusually for normal cells, gastric epithelial cells often carry recurrent trisomies of specific chromosomes, which are highly enriched in a subset of individuals. Surveying 829 polyclonal gastric microbiopsies by targeted sequencing, we find somatic ‘driver’ mutations in a distinctive repertoire of known cancer genes, including ARID1A , ARID1B , ARID2 , CTNNB1 and KDM6A . The prevalence of mutant clones increases with age to occupy roughly 8% of the gastric epithelial lining by age 60 years and is significantly increased by the presence of severe chronic inflammation. Our findings provide insights into intrinsic and extrinsic influences on somatic evolution in the gastric epithelium in healthy, precancerous and malignant states.